(untitled) (Web of Teachers: Inderscience Research, 2026)
This study examines the formation of students’ social competencies through the scientific and methodological foundations of cognitive linguistics in higher education. In modern educational systems, the development of social competence has become as essential as academic achievement. Cognitive linguistics, which explores the interconnection between language, thought, and experience, provides an innovative framework for integrating communicative, conceptual, and reflective skills into the learning process. The research investigates how cognitively oriented instructional strategies influence students’ communicative adaptability, empathy, cooperation, and critical awareness. A semester-long pedagogical intervention was conducted, combining conceptual analysis, metaphor interpretation, reflective practice, and interactive problem-solving tasks. The findings demonstrate significant improvement in students’ social interaction, conceptual understanding, and metacognitive regulation. The study concludes that cognitive linguistics offers an effective methodological basis for fostering socially competent and intellectually autonomous learners in higher education.